A damage tolerance approach for structural integrity of truck trailers. (June 2022) - Huang, Pu; Yin, Yunxiang; McNaulty, Daniel; Yan, Wenyi
Highlights: An approach to investigate fatigue performance of heavy-duty truck trailers based on the damage tolerance concept is proposed. An approach to develop a representative simulated loading spectrum from both multi-body dynamics simulation analysis and static stress analysis is proposed. Simple geometric modification of local regions in trailer structure can improve their fatigue resistance and extend their fatigue life. Damage tolerance approach can be further utilized to improve the structural integrity of truck trailer structures when integrated with an advanced optimization algorithm. Abstract: To understand and analyse fatigue cracking that occurred in heavy truck trailers, a framework based on the damage tolerance concept was proposed to investigate the structural integrity of a high-strength steel trailer structure and to improve its fatigue resistance through local geometric modifications. To illustrate the framework, the fatigue behaviour at a critical region located at a circular cut-out in the trailer was studied. Firstly, a simulated loading spectrum was developed based on the dynamic analysis of a trailer under different driving scenarios together with the FEA analysis of the trailer structure. After that, for the fatigue analysis, crack growth rate at the critical region was computed using the NASGRO equation, and the fatigue life associated with the simulated loading spectrum was predicted. This damage tolerance approach was further applied to explore possible new designs of trailer structures with either improved fatigue performance or reduced tare weight. The results indicate that the proposed framework can be utilised to both monitor the structural integrity of current vehicle structures and design future trailers with longer life and lighter weight.